Uniaxial dry–cold pressing as a rapid specimen fabrication technique aimed at dynamizing the screening of materials of thermoelectric interest: the specific case of Bi2Te3 and TiS2. (28th July 2016) - Lopez, Hugo; Gonzalez, Gabriel; Ramos, Manuel; Chianelli, Russell R.
Abstract : The Bridgman and the chemical vapour transport are crystal growth techniques that are often used to produce high-quality fully dense crystals, but prove impractical for the evaluation of a large number of new compounds. Uniaxial dry–cold pressing (UDCP) is a robust and time-efficient method to agglomerate particulate solids and the work presented here explored it as an alternate sample preparation procedure that will enable rapid thermoelectric evaluation of a large number of new compounds. Samples fabricated by different methods using the chalcogenides Bi2 Te3 (reference compound) and TiS2 (experimental compound) had their Seebeck coefficients and their electrical conductivities measured. It was observed that UDCP pellets generated a good Seebeck coefficient when compared to their monocrystalline counterparts. Manufacturing procedures were developed for fabricating UDCP samples of Bi2 Te3 and TiS2 . The UDCP is a novel technique for the evaluation of new compounds for thermoelectric applications.